2016
DOI: 10.1080/24701394.2016.1214726
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic confirmation of mud crab species (genus Scylla ) in Bangladesh by nuclear and mitochondrial DNA markers

Abstract: Taxonomy of mud crabs genus Scylla has been misidentified for several years due to their high morphological plasticity. Several reports concerning mud crab have been published with misleading identification in Bangladesh. In this study, partial fragments of nuclear and mitochondrial DNA of Scylla species obtained from four locations along the Bangladesh coast were used to resolve taxonomical ambiguity of mud crab species. A single PCR product from the nuclear first internal transcribed spacer (ITS-1) marker an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Our results found that Scylla olivacea was the only species harvested from the mangrove creeks across the Mergui archipelago, in southern Myanmar, as identified using DNA barcoding the first study of its kind in Myanmar’s marine fisheries. This is in accordance with the catch composition of the mud crab fisheries of Malaysia [ 25 ], Bangladesh [ 12 ], and Philippines [ 29 ], where S . olivacea is the only or the dominant species harvests from mangroves fishing grounds.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our results found that Scylla olivacea was the only species harvested from the mangrove creeks across the Mergui archipelago, in southern Myanmar, as identified using DNA barcoding the first study of its kind in Myanmar’s marine fisheries. This is in accordance with the catch composition of the mud crab fisheries of Malaysia [ 25 ], Bangladesh [ 12 ], and Philippines [ 29 ], where S . olivacea is the only or the dominant species harvests from mangroves fishing grounds.…”
Section: Discussionsupporting
confidence: 85%
“…serrata was previously thought to be the most common species harvested across Southeast Asia, but more studies have revealed that S . olivacea is indeed the most common species [ 12 , 15 , 29 ]. Likewise, S. olivacea is the most common species found in the markets in Southeast Asia [ 2 ] and the most important crab for commercial culture in the Indo-West Pacific region leading to high prices in both local and international markets [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although mud crabs have been captured and cultured for over 110 years, the taxonomy of genus Scylla was controversial until the revision by Keenan et al in 1998 [53], based on genetic variations, external morphology and morphometric characters analysis [54]. Phylogenetic study on genus Scylla based on COI sequence of mtDNA showed that S. paramamosain is genetically closest to S. tranquebarica, and then to S. serrata , while, the largest genetic distance was found with S. olivacea [55, 56].…”
Section: Discussionmentioning
confidence: 99%